FRICTION FACTOR CHARACTERISTICS FOR UPWARD SINGLE-PHASE FLOWS INSIDE SMOOTH AND MICROFIN TUBES OF A DOUBLE-PIPE HEAT EXCHANGER FOR HEATING/COOLING CONDITIONS - Cebi, A.; Celen, A.; Dalkilic, A. S.; Wongwises, S. (BEGELL HOUSE INC, 2013)
In this study, single-phase friction factor behavior of smooth and microfin tubes under heating and cooling conditions in a vertical pipe was investigated experimentally. A vertical double-tube heat exchanger in counterflow condition was used as a test section using pure water for both inner and annulus flows. Pressure drop measured by using differential pressure transmitter, and friction factor results were calculated and compared for both heating and cooling conditions and with different tube types. A smooth tube having the equivalent diameter with the microfin tube has been simulated by using two different smooth tube data and used for comparison with a microfin tube. As a result of the analyses, experimental friction factors were found to be in good agreement with those in the literature and correlated with various proposed empirical correlations for each investigated tube. During heating (aiding) conditions of the pure water in the inner tube, friction factors have larger values than those for the cooling (opposing) conditions due to the alteration of physical properties of pure water. Alteration of obtained friction factors by proposed correlations with mass flux and Reynolds number was also given in the paper.
Keywords: rough surfaces; microfins; single-phase flow; diabatic pressure; TURBULENT MIXED CONVECTION; PRESSURE-DROP; BUOYANCY; LAMINAR; EQUATIONS; WATER; Thermodynamics; Engineering